2010
DOI: 10.1007/s11947-010-0421-6
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Starch Separated From Ten Mung Bean Varieties and Seeds Processing Characteristics

Abstract: Starch samples from ten mung bean cultivars grown in china were isolated, and their morphology, physicochemical, thermal, and pasting properties were evaluated. The objectives of the study were to investigate the starch properties and processing characteristics of different mung bean varieties, and to establish the basic foundation of improving the functionality of mung beans and their starch grown in the region. The mung bean starches showed the kidney-shaped, elliptical, small spherical and dome-shaped granu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 33 publications
5
42
2
1
Order By: Relevance
“…Mung bean starch swelled rapidly at a lower temperature than cowpea starch. These pasting temperature results were similar to those of Thao and Noomhorm (2011;Li et al (2011);and Park et al (2012) who reported a range from 71.20 to 76.83°C. Huang et al (2007) noted that cowpea starch had the higher pasting temperature (80°C).…”
Section: Pasting Properties Of Starchsupporting
confidence: 88%
See 1 more Smart Citation
“…Mung bean starch swelled rapidly at a lower temperature than cowpea starch. These pasting temperature results were similar to those of Thao and Noomhorm (2011;Li et al (2011);and Park et al (2012) who reported a range from 71.20 to 76.83°C. Huang et al (2007) noted that cowpea starch had the higher pasting temperature (80°C).…”
Section: Pasting Properties Of Starchsupporting
confidence: 88%
“…The mung bean starch had the highest solubility index at 1.09, 1.17, 1.77, 2.15 and 4.22%, respectively. Similar patterns of solubility for legume starch were observed by Liu and Shen (2007;Huang et al (2007); and Li et al (2011). However, the solubility of some starch mixtures increased rapidly at 85 and 95°C above the pasting temperature.…”
Section: Physical Properties Of Starches Solubility Of Starchsupporting
confidence: 70%
“…Legume starches are characterised by high amylose content, generally found to be greater than 30% of the total starch composition (Hoover & Sosulski, 1991). Li et al (2011) evaluated ten commercial Chinese mungbean cultivars, reporting total starch and amylose content ranging from 54.7-58% and 40.4-41.8%, respectively. Shi et al (2016) evaluated twenty commercial Chinese mungbean cultivars, reporting total starch and amylose content ranging from 40.6-48.9% and 12.5-35.4%, respectively.…”
Section: Starch Composition and Pasting Propertiesmentioning
confidence: 99%
“…Dahiya et al (2013) also investigated the nutritional composition of selected newly bred and established mungbean varieties grown in India. Further studies comparing mungbean varieties grown in both China (Li et al, 2011) and India (Kaur et al, 2011), focussed on starch physicochemical properties, structure and digestibility, reporting varietal variations that can impact processing quality and end-use applications. Varietal differences in protein content, protein isolates and functional properties have also been investigated (Li et al, 2010;Liu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, next to the measurement of the digestibility properties of these starches, the investigations of their rheological, thermal properties can be highly informative for the food industry (Gelencsér et al 2008b). Investigating the physicochemical and structural properties of the starches can provide notable information about the digestibility (Ao et al 2007) and about the specific applicability of starches in food production (Aina et al 2009;Li et al 2010). The physicochemical and chemical characteristics of starches can be analysed using near-infrared (NIR) spectroscopy as well.…”
Section: Introductionmentioning
confidence: 99%